Tourism and geography : links and applications, an analysis from the training of professionals in tourism - Álvarez Meneses, Tannia; Universidad Pedagógica y Tecnológica de Colombia; Herrera López, Beatriz; Gamba Niño, Jorge Enrique; Universidad Pedagógica y Tecnológica de Colombia; Zamora Fernández, María de los Dolores; Martínez del Vas, Ginesa; Nuevo López, Abraham; Flores Domínguez, Ángel David; Ríos Elorza, Serafín; Salazar Monsalve, Luis Fernando; Carrasco Romero, Víctor Josaphat (UPTC Editorial, 2022)
This manuscript is the result of the work of the Research Network between universities in Colombia, Mexico and Spain, led by the Pedagogical and Technological University of Colombia -UPTC and the GUIA Research Group- under the objective of reflecting on the points meeting of the study of geography, its theoretical, conceptual and methodological elements that must be incorporated into the curriculum and study plans of the tourism degree and undergraduate of each of the participating Higher Education Institutions. Each program applied particular methodologies that account for the importance of the study of human geography and geography of tourism, its transversality in the curricula in relation to the concepts and theoretical foundations; also on teaching methods, which required documentary analysis and the opinions of teachers in the area and perceptions of tourism students. From the Permanent Seminar on Tourism of the Network, which was organized virtually and face-to-face, the research results of each Higher Education Institution were presented and the guidelines for the integration methodology of this book were established. The findings presented range from the results of analysis on the approach of the geographic discipline in tourism programs in the case of Colombia and Mexico, to a deeper and more detailed one for Spain, on the presence of geography in tourism programs, tourism from the antecedents and the institutionality. Case study are integrated, where the accompaniment in the student’s training in the classroom is documented, with the fieldwork of research projects, in rural and urban spaces.